(untitled) (Journal of Solar Energy Research Updates, 2021)
Perovskite solar cells are keeping a very high interest in the solar energy world, with an efficiency in constant rise each year. In this study, we designed a tin-based (Hole Transport Material) HTM perovskite solar cell with the novel architecture Au/CH3NH3SnI3/TiO2/ZnO: Al. A simulation has been carried-out by using the SCAPS-1D solar cell capacitance simulator, which is well adapted to study the solar cell behavior. Through the software tool, we have studied the absorber’s layer thickness effect and the model operating temperature by plugging many varied parameters. The encouraging results of: 20.08% conversion efficiency, 32.76mA/cm² short-circuit current density (Jsc), 0.827 V open circuit voltage (Voc), and a fill factor (FF) of 74.06%, are predicted with the obtained optimal parameters. The results indicate the high aptitude of lead free & HTM perovskite to achieve high efficiency and become a good alternative for the traditional solar cells in the future.